BENDERA MERAH PUTIH DALAM ARAREM (Studi Sosiologis Tentang Makna Simbolik Bendera Merah Putih dalam Upacara Pembayaran Maskawin pada Masyarakat Desa Ambroben, Distrik Biak Kota) - Harto Bernabas Berty Sawen; Pamerdi Giri Wiloso; Elly Esra Kudubun (Cakrawala Jurnal Penelitian Sosial, 2016)
Ararem is a Papuan identity (Ambroben, Biak), meaning of payment process of a dowry. Ararem in the practice "requires" the family and relatives of men marching procession accompanied by dancing and singing usher in dowry to the family home women who want to marry. In this ceremony one of the conditions is the use of Red and White Flag, a symbol of Indonesian national identity. This reality becomes problematic because ararem is not a state ceremony. Some of the findings in this study are: a). the flag is interpreted as a "rubber stamp" function validate dowry delivered by the male to the female; b). Meaningful giver "message" that the dowry was ready paid. So, depth meaning as "means of exchange" and mark the handover of dowry; c). Meaningful appreciation and respect for the new identity, which became Indonesia; d). Meaningful expression of fear and self defense; e) meaningful protection and security. The use of the flag is influenced by several factors, namely: a). Tradition; b). Fear and self-defense; and c). Protection and security. Key words: Red White flag, simbolic, identity, Dowry , Ararem , Ambroben , integration of Papua into Indonesia